1985
DOI: 10.1227/00006123-198510000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Clip Motion during Magnetic Resonance Imaging: In Vivo Experimental Study with Metallurgical Factor Analysis

Abstract: Because of various mechanical, metallurgical, and commercial constraints, aneurysm clips are manufactured from different alloys, including several stainless steel and cobalt alloys. Some of the steels contain volume fractions of the crystal phase known as martensite. Martensitic alloys have body-centered cubic structure, are prone to stress corrosion failure, and are ferromagnetic. Martensitic steel can be displaced like a compass needle when exposed to a magnetic field such as that generated during magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…These factors can greatly influence the MR safety aspects of these implants. While certain aneurysm clips are a contraindication for the MR environment, others classified as nonferromagnetic or weakly ferromagnetic are deemed safe for patients or individuals exposed to MR systems operating at 1.5 Tesla or less (1)(2)(3)(4)(5)8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Aneurysm Clipsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors can greatly influence the MR safety aspects of these implants. While certain aneurysm clips are a contraindication for the MR environment, others classified as nonferromagnetic or weakly ferromagnetic are deemed safe for patients or individuals exposed to MR systems operating at 1.5 Tesla or less (1)(2)(3)(4)(5)8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Aneurysm Clipsmentioning
confidence: 99%
“…Previous reports investigating magnetic qualities of aneurysm clips indicated that aneurysm clips made from stainless steel alloy, Phynox, Elgiloy, commercially pure titanium, and titanium alloy were safe at 1.5 Tesla (1)(2)(3)5,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, as previously discussed, few studies have been performed to evaluate magnetic field interactions for implants in association with MR systems operating above 1.5 Tesla.…”
Section: Aneurysm Clipsmentioning
confidence: 99%
“…Even in that case, safety concerns cannot be excluded. Indeed, the literature reports that some devices once thought to have no ferromagnetic potential have been found to possess some of the qualities of ferrous metal [13,[17][18][19]. Explanations for this phenomenon have included the metallurgical composition of different alloys, heat treatment and the degree of cold working during the manufacturing process.…”
Section: Discussionmentioning
confidence: 99%
“…The previous qualitative studies measuring the magnetic field in the MR unit and the movements of the clips may provide practical information regarding the magnetic characteristics of aneurysm clips (Dujovny et al 1984(Dujovny et al , 1985(Dujovny et al , 1994(Dujovny et al , 1996. However, their results should not be considered fully reliable, for the reasons explained earlier.…”
Section: Synthesismentioning
confidence: 99%